Canada - Ford, Richard, 1944- (New York : Ecco Press, 2012)
In 1956, Dell Parsons' parents robbed a bank; finding himself living in Canada with a violent man, Dell discovers, in this new world of secrets and upheaval, he is not the only one whose past lies on the other side of a border.
Maine author.
Keywords: Bank robberies -- United States -- Fiction; Fugitives from justice -- United States -- Fiction; Families -- Fiction